Fabrication of an effusive molecular beam instrument for surface reaction kinetics - CO oxidation and NO reduction on Pd(111) surfaces - Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Catalysis Letters, 2007)
A simple molecular beam instrument (MBI) was fabricated for measuring the fundamental parameters in catalysis such as, sticking coefficient, transient and steady state kinetics and reaction mechanism of gas/vapor phase reactions on metal surfaces. Important aspects of MBI fabrication are given in detail. Nitric oxide (NO) decomposition and NO reduction with carbon monoxide (CO) on Pd(111) surfaces were studied. Interesting results were observed for the above reactions and they support the efficiency of the MBI to derive the fundamental parameters of adsorption and catalysis. Sustenance of CO oxidation at 400 K is dependent mostly on the absence of CO-poisoning; apparently, CO + O recombination is the rate determining step <= 400 K. NO adsorption measurements on Pd(111) surface clearly indicating a typical precursor kinetics. Displacement of the chemisorbed CO by NO on Pd(111) surfaces was observed directly with NO + CO beams in the transient kinetics. It is also relatively easy to identify the rate-determining step directly from the MBI data and the same was demonstrated for the above reactions.
Keywords: carbon monoxide; catalysis; kinetics; molecular beam; nitric oxide; Pd(111)